21st Century Teaching and Learning: Student Teacher’s Perceptions and Challenges in Higher Education Institutions - Fitriati, Fitriati; Prayudi, Satria (Al-Khawarizmi, 2021)
As information technology rapidly changes workplaces and classrooms, the need for education has shifted from focusing on static skills to the ability to learn in a dynamic environment. Higher education institutions are looking for teaching practices to bridge performance gaps and meet the challenge of ensuring that students are prepared for careers after graduation. During this pandemic, more than 85% of jobs are computer-oriented, but a small percentage of students seek educated qualifications. The skills of the early twentieth century are essential to prepare students for these tasks. The purpose of this research is to determine a consensus on the composition of 21st century skills, measure the views of students and teachers, and determine the challenges students face in the learning process. This was a mix methods study. A perceptual survey accompanied by open-ended questions deepened analysis and understanding. The data was analyzed descriptively and open ended question responses were coded, categorized and analyzed using qualitative data analysis approach. The findings showed student’s the difficulties in developing 21st Century skills.